Repurposing Drugs, Ongoing Vaccine, and New Therapeutic Development Initiatives Against COVID-19 - Saha, Rudra P.; Sharma, Ashish Ranjan; Singh, Manoj K.; Samanta, Saikat; Bhakta, Swarnav; Mandal, Snehasish; Bhattacharya, Manojit; Lee, Sang-Soo; Chakraborty, Chiranjib (Frontiers in Pharmacology, 2020)
As the COVID-19 is still growing throughout the globe, a thorough investigation into the specific immunopathology of SARS-CoV-2, its interaction with the host immune system and pathogen evasion mechanism may provide a clear picture of how the pathogen can breach the host immune defences in elderly patients and patients with comorbid conditions. Such studies will also reveal the underlying mechanism of how children and young patients can withstand the disease better. The study of the immune defence mechanisms and the prolong immune memory from patients population with convalescent plasma may help in designing a suitable vaccine candidate not only for the current outbreak but also for similar outbreaks in the future. The vital drug candidates, which are being tested as potential vaccines or therapeutics against COVID-19, include live attenuated vaccine, inactivated or killed vaccine, subunit vaccine, antibodies, interferon treatment, repurposing existing drugs, and nucleic acid-based vaccines. Several organizations around the world have fast-tracked the development of a COVID-19 vaccine, and some drugs already went to phase III of clinical trials. Hence, here, we have tried to take a quick glimpse of the development stages of vaccines or therapeutic approaches to treat this deadly disease.